FAKTOR-FAKTOR EKONOMI YANG MEMPENGARUHI STATUS KEPEMILIKAN RUMAH DI INDONESIA TAHUN 2017-2022 - Yustie, Renta; Kiak, Novi Theresia; Utami, Betty Silvia Ayu (JURNAL AKUNTANSI : TRANSPARANSI DAN AKUNTABILITAS, 2024)
Home is one of the basic needs for humans. Over time, the function of the house is also growing. Especially in Indonesia, the population is increasing every year, so the need for a place to live is also increasing. This research uses panel data with a sample of 34 provinces in Indonesia with a range from 2017 to 2022. The variables in the study are Home Ownership Status, Gro ss Regional Domestic Product, House Prices and Number of Houses. Calculations using the EViews 9 analysis tool by conducting hypothesis testing and classic assumption tests, it is expected that the variables used in the research are economic factors and have a significant influence and have a positive relationship in home ownership status.